Simplifying
6x + -2 + 2x = -2 + 4x + 8
Reorder the terms:
-2 + 6x + 2x = -2 + 4x + 8
Combine like terms: 6x + 2x = 8x
-2 + 8x = -2 + 4x + 8
Reorder the terms:
-2 + 8x = -2 + 8 + 4x
Combine like terms: -2 + 8 = 6
-2 + 8x = 6 + 4x
Solving
-2 + 8x = 6 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
-2 + 8x + -4x = 6 + 4x + -4x
Combine like terms: 8x + -4x = 4x
-2 + 4x = 6 + 4x + -4x
Combine like terms: 4x + -4x = 0
-2 + 4x = 6 + 0
-2 + 4x = 6
Add '2' to each side of the equation.
-2 + 2 + 4x = 6 + 2
Combine like terms: -2 + 2 = 0
0 + 4x = 6 + 2
4x = 6 + 2
Combine like terms: 6 + 2 = 8
4x = 8
Divide each side by '4'.
x = 2
Simplifying
x = 2